'fountains frozen o'er': Samuel Beckett's Atavistic Translations. Issue 2 (September 2019) - Kenny, Eva
Abstract : Increasing importance has been placed on Samuel Beckett's work as a translator in recent years. Here I look at his translation of the French surrealists into English in the Surrealist Issue of the avant-garde journal This Quarter, and develop the argument made in Pascale Sardin and Karine Germoni's excellent 2011 study, 'Scarcely Disfigured: Beckett's Surrealist Translations', from which I take many cues. In what follows, I propose a theory of Beckett's translation: that literary atavism, models of arrested development and recursive strategies were central to the Irish writer's work, and that he developed these in his translations, in the ways that he preserved the past in his surreal translations, learning to become what André Breton called 'the silent receptacle of many echoes'.